Hypoxia-Induced Differences in the Expression of Pyruvate Dehydrogenase Kinase 1-Related Factors in the Renal Tissues and Renal Interstitial Fibroblast-like Cells of Yak (Bos Grunniens) - Manlin Zhou; Jun Wang; Ruirui Cao; Fan Zhang; Xuehui Luo; Yiyuan Liao; Weiji Chen; Haie Ding; Xiao Tan; Zilin Qiao; Kun Yang (Animals, 2024)
Hypoxia is one of the factors severely affect renal function, and, in severe cases, it can lead to renal fibrosis. Although much progress has been made in identifying the molecular mediators of fibrosis, the mechanisms that govern renal fibrosis remain unclear, and there have been no effective therapeutic anti-fibrotic strategies to date. Mammals exposed to low oxygen in the plateau environment for a long time are prone to high-altitude disease, while yaks have been living in the plateau for generations do not develop kidney fibrosis caused by low oxygen. It has been suggested that metabolic reprogramming occurs in renal fibrosis and that pyruvate dehydrogenase kinase 1 (PDK1) plays a crucial role in metabolic reprogramming as an important node between glycolysis and the tricarboxylic acid cycle. The aim of this study was to investigate the effects of hypoxia on the renal tissues and renal interstitial fibroblasts of yaks. We found that, at the tissue level, HIF-1α, PDK1, TGF-β1, Smad2, Smad3, and α-SMA were mainly distributed and expressed in tubular epithelial cells but were barely present in the renal mesenchymal fibroblasts of healthy cattle and yak kidneys. Anoptical density analysis showed that in healthy cattle kidneys, TGF-β1, Smad2, and Smad3 expression was significantly higher than in yak kidneys (p < 0.05), and HIF-1α and PDK1 expression was significantly lower than in yak kidneys (p < 0.05). The results at the protein and gene levels showed the same trend. At the cellular level, prolonged hypoxia significantly elevated PDK1 expression in the renal mesangial fibroblasts of cattle and yak kidneys compared with normoxia (p < 0.05) and was proportional to the degree of cellular fibrosis. However, PDK1 expression remained stable in yaks compared with renal interstitial fibroblast-like cells in cattle during the same hypoxic time period. At the same time, prolonged hypoxia also promoted changes in cellular phenotype, promoting the proliferation, activation, glucose consumption, lactate production, and anti-apoptosis in the both of cattle and yaks renal interstitial fibroblasts The differences in kidney structure and expression of PDK1 and HIF-1α in kidney tissue and renal interstitial fibroblasts induced by different oxygen concentrations suggest that there may be a regulatory relationship between yak kidney adaptation and hypoxic environment at high altitude. This provides strong support for the elucidation of the regulatory relationship between PDK1 and HIF-1α, as well as a new direction for the treatment or delay of hypoxic renal fibrosis; additionally, these findings provide a basis for further analysis of the molecular mechanism of hypoxia adaptation-related factors and the adaptation of yaks to plateau hypoxia.